Chosen Vascular Risk Markers in Pseudoexfoliation Syndrome: An Age-Related Disorder. (31st October 2017) - Lesiewska, Hanna; Łukaszewska-Smyk, Agnieszka; Odrowąż-Sypniewska, Grażyna; Krintus, Magdalena; Mańkowska-Cyl, Aneta; Malukiewicz, Grażyna
Abstract : Purpose . To evaluate lipids and C-reactive protein serum levels in patients with pseudoexfoliation syndrome (PEX) in the Polish population. Methods . 96 patients were studied with PEX and 79 control subjects. Total cholesterol, triglycerides, high-density lipoprotein (HDL)-cholesterol, low-density lipoprotein (LDL)-cholesterol, non-HDL-cholesterol and CRP serum levels, and TG/HDL-C and TC/HDL-C indexes were assessed. Results . There were no significant differences in concentration of lipids and values of TC/HDL-C, TG/HDL-C, and non-HDL-C between PEX and control groups. High-sensitivity C-reactive protein was not increased in patients with PEX. Conclusions . Our results cast doubt on the opinion on the possible PEX and vascular diseases relation. Further studies on this subject are mandatory.